QUALITY RETENTION IN ALUM TREATED BAEL (AEGLE MARMELOS CORR.) PRESERVE - AMIT KUMAR SINGH; A. K. CHAURASIYA; I. CHAKRABORTY (The Bioscan, 2014)
Bael preserve was prepared with combination of sugar, acid, water and preservative and two cultivars of bael like Local cultivar of West Bengal and NB-5 with a large fruit of greenish yellow to yellowish green, average fruit weight (723.50 and 1212.50g), pulp per cent (75.40 and 79.62), TSS (12.2 and 14.4 ºBrix), ascorbic acid (13.12 and 27.36 mg/100 g pulp) and â carotene (1868.01 and 1155.37 IU) were used in the study. The slices were dipped in alum solution (2 per cent) for two hours and blanched, were found best recipe of bael preserves. Further the product was stored at room (25-37ºC) and refrigerated temperatures (8-10ºC) up to 7 and 12 months as well as organoleptic score 4.82 and 4.90 was found best among all treatments of local and NB-5 cultivars respectively.